Molecular light scattering and optical activity - Barron, L. D. (Cambridge University Press, 2004)
Using classical and quantum methods with a strong emphasis on symmetry principles, this book, a reissue of the 2004 second edition, develops the theory of a variety of optical activity and related phenomena from the perspective of molecular scattering of polarised light. In addition to the traditional topic of optical rotation and circular dichroism in the visible and near-ultraviolet associated with electronic transitions, the newer topic of optical activity associated with vibrational transitions, which may be studied using both infrared and Raman techniques, is also treated. Ranging from the physics of elementary particles to the structure of viruses, the subject matter of the book reflects the importance of optical activity and chirality in much of modern science and will be of interest to a wide range of physical and life scientists.